2006
DOI: 10.1007/s11240-006-9129-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficient plant regeneration from protoplasts isolated from embryogenic suspension cultures of Cyclamen persicum Mill.

Abstract: A protocol for plant regeneration from protoplasts has been developed, and then successfully applied to different genotypes of Cyclamen persicum Mill. Protoplasts were isolated from embryogenic suspension cultures by enzymatic digestion in 2% cellulase R10 and 0.5% macerozyme R10. Yields obtained varied between 1 and 5 · 10 5 protoplasts per gram fresh mass depending on the genotype. Protoplasts were immobilized in alginate films, which promoted proper cell wall regeneration. The highest cell division frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
(33 reference statements)
0
15
0
Order By: Relevance
“…1). In contrast, Cyclamen suspension-derived protoplasts grew better in alginate than in liquid culture (Winkelmann et al 2006). Previously, it has been reported that Saintpaulia protoplasts required support of the alginate matrix and did not develop microcalluses in agarose culture (Winkelmann and Grunewaldt 1992).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…1). In contrast, Cyclamen suspension-derived protoplasts grew better in alginate than in liquid culture (Winkelmann et al 2006). Previously, it has been reported that Saintpaulia protoplasts required support of the alginate matrix and did not develop microcalluses in agarose culture (Winkelmann and Grunewaldt 1992).…”
Section: Discussionmentioning
confidence: 87%
“…Changes in chlorophyll synthesis are not uncommon in in vitro cultures (Winkelmann and Grunewaldt 1995;Winkelmann et al 2006). These can be caused by different factors such as temperature during the culture period (Ouyang et al 1983), KNO 3 concentration of the medium during the callus growth phase (Feng and Ouyang 1988), or due to inappropriate levels of such PGRs as 2,4-dichlorophenoxyacetic acid (2,4-D; Creemers-Molenaar et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Kocak et al (2014) reported the most efficient acclimatization resulted in a survival percentage of 38.8 % in wild C. persicum. Winkelmann et al (2006) observed 41 % acclimatization frequency, lower than 80-95 % frequency obtained from ovule of somatic embryo-derived C. persicum plants. The survival ratio of plantlet was reported by other researchers: 42 % (Geier 1977), 95 % (Murasaki and Tsurushima 1988), 90 % (Otani and Shimada 1991).…”
Section: Evaluation Of Plantlet Formation and Acclimatizationmentioning
confidence: 56%
“…(Schwenkel and Grunewaldt 1988;Al-Majathoub 1999;Al-Majathoub and Karam 2000;Karam and Al-Majathoub 2000a, b;Abu-Qaoud 2004;Jalali et al 2012;Nhut et al 2012), but also for C. mirabile (Yamaner and Erdag 2008). Somatic embryogenesis has been found to be an efficient system for the in vitro propagation of C. persicum ; Motoyasu and Takiko 1991;Kreuger et al 1995;Schwenkel and Winkelmann 1998;Ruffoni et al 1998;Hohe et al 1999a, b;Winkelmann et al 2003;Winkelmann and Serek 2005;Winkelmann et al 2006;Naderi et al 2012;Kocak et al 2014). Only few reports have dealt with somatic embryogenesis or the formation of embryo-like structures (ELSs) in wild Cyclamen species, namely C. cilicium and C. mirabile (Furukawa et al 2001(Furukawa et al , 2002Seyring et al 2009;Prange et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…GGMOs are able to influence developmental processes of spruce embryos [8], division and differentiation of cells [9], and viability and regeneration capacity of spruce protoplasts [10]. The success of protoplast regeneration is determined by cells viability and ability to synthesize new cell walls and to divide, but the rapidity of cell wall formation is influenced by many exo-and endogenous factors [11][12][13][14][15]. As galactoglucomannan oligosaccharides are components of primary and secondary cell walls of conifers, it was of interest to study the effect of GGMOs, as biologically active molecules, on spruce protoplasts.…”
Section: Introductionmentioning
confidence: 99%